2018
DOI: 10.1002/lno.11016
|View full text |Cite
|
Sign up to set email alerts
|

Living in a browning environment: Effects on Daphnia’s growth and fatty acid pattern

Abstract: To assess whether different concentrations of dissolved organic matter (DOM) rich in humic substances (HS) affect growth rates, reproduction and fatty acids (FA) composition of Daphnia pulex under bright light, we performed microcosms controlled laboratory trials. Experiments were run using two microalgae as food source, Cryptomonas erosa and Scenedesmus acutus at four DOM additions (0 mg C L−1, 15 mg C L−1, 30 mg C L−1, and 60 mg C L−1) under unlimited food concentrations. Results show that daphnids’ growth r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 77 publications
0
6
0
Order By: Relevance
“…They also suggest that Daphnia reared at 12°C versus 20°C may not be nutritionally very different to Chaoborus . Previous studies have shown that Daphnia fatty acid profiles mimic those of their diet, and also that Daphnia can synthesize a small fraction of PUFA de novo (Gladyshev et al., 2016; Nova et al., 2019). Chaoborus americanus have a 1‐year life cycle and they remain in larval form from late summer to the following spring (Fedorenko & Swift, 1972).…”
Section: Discussionmentioning
confidence: 99%
“…They also suggest that Daphnia reared at 12°C versus 20°C may not be nutritionally very different to Chaoborus . Previous studies have shown that Daphnia fatty acid profiles mimic those of their diet, and also that Daphnia can synthesize a small fraction of PUFA de novo (Gladyshev et al., 2016; Nova et al., 2019). Chaoborus americanus have a 1‐year life cycle and they remain in larval form from late summer to the following spring (Fedorenko & Swift, 1972).…”
Section: Discussionmentioning
confidence: 99%
“…Contrary to our expectations, DOC had no effects on hatching patterns when in direct contact with resting eggs. DOC is acknowledged to directly affect several life history parameters of cladocerans, as HS may be taken up by organisms and interact with biochemical constituents and signaling pathways (Steinberg et al, 2006;Suhett et al, 2011;Nova et al, 2018). Additionally, DOC may dye the body surface of cladocerans turning them darker.…”
Section: Discussionmentioning
confidence: 99%
“…Organic carbon (OC) concentrations and water colour have been reported to increase in surface waters in the boreal and nemoral zones of Europe and North America. This so-called "brownification" of water bodies can affect aquatic food web structures [17,18], have implications for drinking water treatment [19,20], and mobilize pollutants and metals attached to organic molecules [21,22]. Land use activities, such as forest harvest and peatland drainage, have been found to increase the concentrations and loads of DOC in surface waters (e.g., [4,[23][24][25]).…”
Section: Introductionmentioning
confidence: 99%